2016
DOI: 10.3233/bmr-160713
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of Mulligan's mobilization and Kinesio taping on pain, range of motion, muscle strength, and neck disability in patients with Cervical Spondylosis: A randomized controlled study

Abstract: KT and MM contributed to CR for increasing cervical ROM and deep cervical flexor muscle strength in patients with CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…The KT method could have positive effects on non-structural spine deviations (paramorphism) as a preventive method before these deviations become structural (dysmorphisms), even if in the current literature there is a lack of studies to confirm and strengthen this hypothesis. However, some studies have not been conducted on a sufficiently large cohort of patients to give statistically significant results [15,32,33,44,[68][69][70]. Furthermore, it is necessary to also consider the non-standardized KT applications where application is done according to the therapist or practitioner's discretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KT method could have positive effects on non-structural spine deviations (paramorphism) as a preventive method before these deviations become structural (dysmorphisms), even if in the current literature there is a lack of studies to confirm and strengthen this hypothesis. However, some studies have not been conducted on a sufficiently large cohort of patients to give statistically significant results [15,32,33,44,[68][69][70]. Furthermore, it is necessary to also consider the non-standardized KT applications where application is done according to the therapist or practitioner's discretion.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported also by Parreira and coauthors [43], who found no significant effects on pain intensity, or disability from using the KT method, regardless of the application technique. Postural control of the lower back is positively affected by KT application as well [30,33,36,37,44]. A study conducted on sacroiliac joint dysfunction showed that the KT method balances pelvic inclination and sacral horizontal angle, thereby influencing postural control [30].…”
Section: Kinesio Taping and Spinementioning
confidence: 99%
“…Por otro lado, al aplicar el VPN se ha evidenciado un efecto estadísticamente significativo en cuanto a cambios en la limitación funcional del paciente, hallazgo del que también informan Copurgensli (27) , Saavedra-Hernández (28) , Saavedra-Hernández (29) y Kavlak (30) . La limitación funcional es un problema causado por el dolor cervical, por lo que es necesario conocer los factores que influyen sobre la capacidad funcional ya que una intervención temprana evitaría la progresión de la discapacidad, mejoraría el estado de salud y la calidad de vida, con el desarrollo de estrategias para mitigar este problema (31) .…”
Section: Discussionunclassified
“…Results of their study showed that the MMT and kinesio taping have no additional effects on neck pain, muscle strength, and neck-related disability. Furthermore, they said that the use of the MMT and kinesio taping in addition to conventional rehabilitation, the gain in cervical ROM, and deep cervical flexor muscle strength may be increased in patients with cervical spondylosis (level of evidence = 1B) [ 32 ]. These studies are generally randomized controlled (level of evidence = 1B) studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are generally randomized controlled (level of evidence = 1B) studies in the literature. In comparison studies of the MMT with other treatments there are different opinions about whether it is effective or not [ 4 , 23 , 31 , 32 ]. In our study, older adults aged 65 years and over were included, and the MMT has been found to have significant effects on pain, ROM, functional level, kinesiophobia, depression, and QoL.…”
Section: Discussionmentioning
confidence: 99%